Intramuscular Olanzapine in the Management of Behavioral and Psychological Symptoms in Hospitalized Older Adults: A Retrospective Descriptive Study - Silvia Duong; Kam-Tong Yeung; Feng Chang (Journal of Aging Research)
Background. While behavioral and psychological symptoms are frequent in hospitalized older adults with dementia or delirium, data supporting the off-label use of intramuscular atypical antipsychotics remain scarce. We examined the use of short-acting intramuscular (IM) olanzapine in hospitalized older adults to manage behavioral and psychological symptoms. Methods. A retrospective observational study of inpatients 65 years or older with at least one order for olanzapine IM during admission in urban Ontario Canada was conducted. Patient demographics, prescriptions for olanzapine IM, reason for administration, perceived effectiveness, adverse events, concurrently prescribed psychotropics, comorbidities, and patient discharge destination were recorded. Results. Among 82 patients aged 65–96 years (mean ± SD 79.3 ± 7.7) 85 cases were identified. Cognitive impairment or dementia affected 63.5% and 50.6% had comorbidities. Olanzapine IM was ordered 102 times and 34 patients (41%) received at least one dose. The intended efficacy was achieved in 79.4% of 78 cases of 124 doses given (62.9%). Fourteen (41%) patients who received doses experienced adverse events, with sedation and hypotension being the most common. Conclusions. Olanzapine IM appears effective in hospitalized older adults but is associated with potential adverse events. Structured monitoring and documentation are needed to ensure safe use in this high-risk population.